Primary Leiomyosarcoma of the inferior vena cava – radical resection and vaskular reconstruction – case report - Petrovic, Ognjen; Srđan,; Djurisic, Igor; Kocic, Milan; Babic, Andjela; Jokic, Vladimir; Pejnovic, Luka; Vucic, Nikola; Gacic, Stefan; Rajacic, Lila (Medical Research, 2024)
Introduction: Sarcomas are rare tumors that account for less than 1% of malignant tumors in adults. Primary leiomyosarcoma of the inferior vena cava is a very rare tumor with an incidence of
Keywords: leiomyosarcoma; vena cava inferior; sarcoma; suregery